Catheter-Related ESBL-Producing Leclercia adecarboxylata Septicemia in Hemodialysis Patient: An Emerging Pathogen? - Roaa Sultan Alosaimi; Mai Muhmmed kaaki (Case Reports in Infectious Diseases)
We report a multidrug-resistant strain of Leclercia adecarboxylata which was responsible for a catheter-related bacteremia, in a 50-year-old female with an end-stage renal disease on hemodialysis. The isolated strain was an extended beta-lactamase producer. Based on a literature review of L. adecarboxylata, there have been only two reports of extended beta-lactamase producer strains. To our knowledge, this is the first case reported in Saudi Arabia.